Advantages of Using Modern Learning Technologies in the System of Vocational Education - Mustafoyevа Durdonа (European Journal of Life Safety and Stability (2660-9630), 2021)
Middle-class specialists have always played an important role in the development of the state and society, in building the potential of the production and service sectors. In the case of interpretation, they are considered an important balancing force in ensuring the "golden mean" of socio-economic processes. This is a vital fact that has been confirmed not only in history, but also in today’s practice. In particular, the role and value of qualified specialists who are trained precisely in the conditions of a pandemic is becoming obvious.